Age-adjusted high-sensitivity troponin T cut-off value for risk stratification of pulmonary embolism - Käberich, Anja; Giannitsis, Evangelos (The European respiratory journal, 2015)
High-sensitivity troponin T (hsTnT) helps in identifying pulmonary embolism patients at low risk of an adverse outcome. In 682 normotensive pulmonary embolism patients we investigate whether an optimised hsTnT cut-off value and adjustment for age improve the identification of patients at elevated risk. - Overall, 25 (3.7%) patients had an adverse 30-day outcome. The established hsTnT cut-off value of 14 pg·mL−1 retained its high prognostic value (OR (95% CI) 16.64 (2.24-123.74); p=0.006) compared with the cut-off value of 33 pg·mL−1 calculated by receiver operating characteristic analysis (7.14 (2.64-19.26); p<0.001). In elderly (aged ≥75 years) patients, an age-optimised hsTnT cut-off value of 45 pg·mL−1 but not the established cut-off value of 14 pg·mL−1 predicted an adverse outcome. An age-adjusted hsTnT cut-off value (≥14 pg·mL−1 for patients aged <75 years and ≥45 pg·mL−1 for patients aged ≥75 years) provided additive and independent prognostic information on top of the simplified pulmonary embolism severity index (sPESI) and echocardiography (OR 4.56 (1.30-16.01); p=0.018, C-index=0.77). A three-step approach based on the sPESI, hsTnT and echocardiography identified 16.6% of all patients as being at higher risk (12.4% adverse outcome). - Risk assessment of normotensive pulmonary embolism patients was improved by the introduction of an age-adjusted hsTnT cut-off value. A three-step approach helped identify patients at higher risk of an adverse outcome who might benefit from advanced therapy. - Tweetable abstract ERSpublications - click to tweetAge-adjusted hsTnT cut-off values for risk stratification of pulmonary embolism provide additive prognostic information. http://ow.ly/FmcZl
Gesehen am 17.06.2020